Methodological problems of the scientific theories analyses - V. P. Kotenko (Библиосфера, 2013)
The methodological problems of scientific theory are considered. The notion of a scientific theory is analyzed. The principles of classification of scientific theories including internalist, externalist and system theories are revealed.